Male novices' conscious religious motivation, aspects and maturity, and their correlates - Sabandal, Amparo K. (Animo Repository, 1986)
The purpose of this study was to investigate and present a descriptive profile of the novices' level of aspects of maturity and conscious religious motivation through the use of two instruments, the California psychological inventory (CPI) and the Religious motivation index (RMI). The study tried to determine if there were significant differences in the levels of maturity and conscious religious motivation according to variables of age, educational attainment and number of years stay in the seminary. The subjects (N = 119) were drawn from 7 out of 14 member - congregations of the Association of Men Novitiates in Metro Manila who responded favorably to the researcher's request. The descriptive method of research was the main research design. To determine the profiles on both the CPI and the RMI, means and standard deviations were computed for each factor. The t-test was used to test for differences between means and the Pearson r to test the relationships between levels of maturity and motivation. The levels of Maturity and Conscious Religious Motivation were found to be low to high and low average to above-average levels, respectively. The older novices showed higher mean scores than the younger ones. The number of years stay in the seminary yielded differences in scores in Dominance, Self-Acceptance, Socialization and Achievement via Conformance. The longer the novices's stay in the seminary, the higher were their scores on these areas.Educational attainment showed differences in scores in dominance and self-Control. Novices who are college graduates had higher scores on these areas than those who have not yet finished college. Of the 10 motivation factor scores, only decision-making was not affected by age, educational attainment and number of years' stay in the seminary. All subjects rated low in this area. The older novices, those who are college graduates, and those who have stayed in the Seminary longer, had significantly higher means on dominance, responsibility, achievement via conformance, socialization and self-Acceptance. Self-Control showed a similar trend on age and educational attainment grouping. Those who had 1-3 years' stay in the Seminary, showed higher Self-Control mean than those who stayed longer. Hence, hypothesis number one, which states that, based on the variables of age, number of years' stay in the seminary and educational attainment, there are no significant differences in the novices levels of maturity as measured by CPI, was rejected. Only the Motivation score on Responsibility had a significantly higher mean for the 28-34 age group. Thus, hypothesis number two, which states that, based on the variables of age, number of years' stay in the seminary and educational attainment, there are no significant differences in the novices religious motivation scores as measured by RMI, was rejected. Nine Maturity scores and seven Motivation factor scores showed substantial and significant correlations. Hence, hypothesis number three, which states that there is no significant relationship between levels of certain aspects of maturity as measured by CPI and the religious motivation as measured by RMI, was rejected.